Kompleks Batuan Ultramafik Meratus sebagai bagian dari Ofiolit Kerak Samudera Ditinjau dari Aspek Geomagnetik dan Gaya Berat - Budi Setyanta; Imam Setiadi (Pusat Survei Geologi, 2006)
Geomagnetic and gravity analyses were carried out in the Banjarmasin quadrangle, South Kalimantan. Qualitative analysis of gravity anomaly show that ophiolite is located in the central quadrangle with anomaly values between 550 µms-2 and 750 µms-2 trending southwest-northeast.Geomagnetic qualitative analysis presents high geomagnetic anomaly part values between 0 nT and 450 nT in the southern area, while low anomaly between -750 nT to 0 nT, generally in northern part of the sheet. Quantitative analysis was done by making subsurface geological profiles model AB, CD, and EF. Ophiolite rock from the gravity modeling have density between 2.7 gr/cc and 2.9 gr/cc. This is probably caused by fragmentation process which affect the basement oceanic rock mix by Pre-Cretaceous rock such as chert, metamorphic and carbonat rocks, accordingly this reduce the rock density, while geomagnetic model have susceptibility of 0.15 SI. Ophiolite rock was interpreted as oceanic crust bolder that overlay on the granitic crust which has less magnetization. This shows a subduction model which cause oceanic crust uplifted and laid on the upper of granitic crust and than revealed as Bobaris and Manjam ophiolite belts. Keywords : Geomagnetic, gravity, ophiolite, oceanic crust